Implementasi Pendidikan Agama Berbasis Multikultural untuk Mengembangkan Sikap Toleransi Beragama Siswa di SD Negeri Ngasemlemahbang - Mariska, Devi Dwi; Huda, Saihul Atho Alaul; Waslah, Waslah (Lembaga Yasin AlSys, 2025)
Religious tolerance issues in multicultural elementary school environments remain a significant challenge, particularly in pluralistic societies like Indonesia, where disharmony may arise without early cultivation of mutual respect. This study aims to explore the implementation of multicultural-based religious education in fostering students’ attitudes of religious tolerance at SDN Ngasemlemahbang, a school characterized by religiously heterogeneous social settings. A qualitative descriptive approach was employed, with data collected through observation, interviews, and documentation involving the principal, Islamic and Christian religious teachers, and fifth- and sixth-grade students as research subjects. Data analysis proceeded through data condensation, presentation, and conclusion drawing. The findings reveal that multicultural-based religious education was implemented through segregated religious classes according to students’ faiths, habituation of religious activities, and interfaith interactions within the school environment. These strategies successfully enhanced students’ understanding and mutual respect across different religious backgrounds. In conclusion, a multicultural approach to religious education is effective in nurturing religious tolerance attitudes at the elementary school level. The implication is that this educational model can serve as a reference for other schools with similar diversity to create an inclusive, peaceful, and harmonious educational environment.